Manajemen Keuangan Dalam Meningkatkan Mutu Pendidikan - Nurdiana, Defi Dachlian; Nadifah, Nur Izzatin (PT. Cahya Edupreneur Indonesia, 2023)
This article is the result of field research at UPT One Roof State Junior High School schools. The focus of the research being studied is on school financial planning and school financial management at UPT One-Roof Public Middle Schools. This study aims to find out how financial planning and management is done at UPT SMP Negeri One Roof schools. The research method used is a qualitative method. This primary data collection method was carried out by observation, interviews, and documentation with the school treasurer. while the secondary data in this study used books, journals, and sources from the internet as a support. The results of this study indicate that the source of school funds comes from BOS and APBD funds and that financial planning follows the arches and financial management through planning which is the responsibility of the school principal.